Water quality and microbiological risk associated with multiple antibiotic resistance (MAR) bacteria in water of fish facility - Lee, K.S.; Kong, C.Y.; Toh, S.C.; Samuel, L. (Universiti Putra Malaysia, 2016)
Fish can live healthier in aquarium with good water quality than they do in the wild. Maintaining the quality of the water in fish facility is needed to avoid fluctuation of physicochemical parameter values and contamination with pathogenic microorganisms that may cause serious illness or even death among the fish. Contamination of the water, especially with animal pathogens which are also pathogenic to human may pose health risk to those who are handling or in direct contact with the water and fish in the facility. Therefore, there is a need to assess the water quality and the risk associated with microorganisms in the water and the cultured animals. The aim of this study was to determine the water quality with regard to the physicochemical and microbiological parameters as well as the risk associated with bacteria in the water of the fish facility. Samples of water from the water source and also from aquariums in the fish facility were collected and analyzed. The water samples were plated on nutrient agar for bacterial enumeration then bacterial colonies growing on the agar plates were randomly picked and purified. (GTG)5-PCR analysis was carried out to analyse the heterogeneity of the genome of the bacterial isolated and a dendrogram was constructed from the (GTG)5-PCR profile to determine the genotypic group of the bacterial isolates. The risk associated with the bacteria from the water was analyzed with respect to their antibiotic resitance. The result of this study revealed that the (GTG)5-PCR analysis was able to group the bacteria into 2 main genotypic clusters which were further grouped into several sub-clusters. From the dengrogram, 12 representative isolates were selected and identified using 16S rRNA sequencing. The identification confirmed the presence of Aeromonas veronii (8 isolates), Aeromonas jandaei (2 isolates), Plesiomonas shigelloides (1 isolate) and Pseudomonas alcaligene (1 isolate) from the water samples. All of the isolates exhibited resistant towards ampicillin, penicillin and gentamicin. This study revealed that the water from the fish facility harboured genetically diverse antibiotic resistance bacteria which may pose health risk to the fish and also to those who are in direct contact with the contaminated water and fish in the facility. Therefore, water in fish facility should be monitored regularly and handled with caution.